Answer:
(2x+1)(x-3) is the factorized form of the given expression
Step-by-step explanation:
=2x^2-5x-3
By using sum and product rule
=2x^2-6x+1x-3
By taking common
=2x(x-3)+1(x-3)
=(2x+1)(x-3)
I hope this will help you :)
Answer:
y = 12-(61) is the answer !!
Answer:b
Step-by-step explanation:it equals out to 180°
Answer: Look below. I hope this helps=3
Step-by-step explanation: Sales tax is an additional amount of money you pay. based on a percentage of the selling price of goods. Also services that are purchased. For example, if you purchase a new television for $400 and live in an area where the sales tax is 7%. Then you would pay $28 in sales tax.